2022
DOI: 10.5194/hess-26-4587-2022
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing basin-scale precipitation gradients in the Third Pole region using a high-resolution atmospheric simulation-based dataset

Abstract: Abstract. Altitudinal precipitation gradient plays an important role in the interpolation of precipitation in the Third Pole (TP) region, where the topography is very complex but in situ data are very sparse. This study proves that the altitude dependence of precipitation in the TP can be reasonably reproduced by a high-resolution atmospheric simulation-based dataset called ERA5_CNN. The precipitation gradients, including both absolute (APGs) and relative gradients (RPGs), for 388 sub-basins of the TP above 25… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Meteorological stations across the AWT are usually located in valleys or low-elevation locations for the convenience of data reading and instrument maintenance as a result, precipitation gauges at lower elevations tend to miss precipitation occurring at higher elevations which leads to underestimations of precipitation within grid cells ( 11 ). These errors are further amplified due to the existence of a considerable vertical precipitation gradient (up to a certain elevation) found in the majority of AWT regions, particularly during the prevalent snowfall months of winter and spring ( 12 ), and the gradient for the increase in precipitation with elevation was estimated typically in the range of 0.05 to 0.5% m −1 ( 13 ). A comparison of the elevation of the meteorological station and the corresponding elevation of the grid cell where the station site is located revealed that the median elevation of existing meteorological stations across the AWT is ~1 km lower than the average elevation of the corresponding grid cells (0.5° × 0.5°) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meteorological stations across the AWT are usually located in valleys or low-elevation locations for the convenience of data reading and instrument maintenance as a result, precipitation gauges at lower elevations tend to miss precipitation occurring at higher elevations which leads to underestimations of precipitation within grid cells ( 11 ). These errors are further amplified due to the existence of a considerable vertical precipitation gradient (up to a certain elevation) found in the majority of AWT regions, particularly during the prevalent snowfall months of winter and spring ( 12 ), and the gradient for the increase in precipitation with elevation was estimated typically in the range of 0.05 to 0.5% m −1 ( 13 ). A comparison of the elevation of the meteorological station and the corresponding elevation of the grid cell where the station site is located revealed that the median elevation of existing meteorological stations across the AWT is ~1 km lower than the average elevation of the corresponding grid cells (0.5° × 0.5°) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, due to the limitation of available weather stations, some related issues such as the effects of altitudinal precipitation gradient (Jiang et al., 2022) and diurnal characteristics of sub‐daily precipitation (Li, 2018; Zipser & Xu, 2011), cannot be fully taken into account in this study. Future studies considering these could further improve the quality of the parameters data set generated.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Previous research on the Qinghai-Tibet Plateau has shown that the relative precipitation gradient (RPG) generally decreases with increasing relative humidity, while there is a high positive correlation between wind speed and RPG (Jiang et al 2022). In this study, we investigated the impact of these two meteorological factors on PGs.…”
Section: The Relationship Between Pg and Relative Humidity And Wind S...mentioning
confidence: 94%
“…However, there are few studies on the vertical gradient of precipitation based on the Tianshan and Qilian Mountains in the arid northwest region. Large-scale changes in precipitation at the spatial scale are mainly affected by atmospheric circulation mechanisms, while relatively small-scale regional and local precipitation changes mainly rely on local terrain (Jiang et al 2022). Using yearly or monthly time scales to study the precipitation-altitude relationship is more effective (Guo et al 2022), which highlights the importance of studying the spatial and temporal changes in PG at yearly and monthly scales after regional division and is conducive to a deeper understanding of the characteristics of mountain precipitation changes in the northwestern region of China.…”
Section: Introductionmentioning
confidence: 99%